New Business Models And Editorial Exemption: A Study On Service Journalism Based On Ecommerce Operations - Belda, Francisco Rolfsen [UNESP] (My University, 2014)
The paper presents and discusses business strategies based on the association from journalistic content to new commercial practices in digital media. We describe selected examples from Folha de S. Paulo and El País involving service guides, links and ecommerce advertisements. The employed method provides content analysis to illustrate how the search for new business models in journalism may conduct its commercial activities beyond the conventional sale of advertising and subscriptions, including a discussion on the challenges and implications of this practice. The hypothesis is demonstrated by describing operations for the sale of tickets, books, music, and films related to news features and service journalism contents. The text finally wonders and discusses how such commercial actions may affect editorial autonomy and publishing exemption.

O trabalho apresenta e discute estratégias de negócios baseadas na vinculação de conteúdos jornalísticos a novas modalidades comerciais nos cibermeios. São descritos exemplos selecionados de Folha de S. Paulo e El País envolvendo guias de serviço, links patrocinados e anúncios de comércio eletrônico. O método emprega análise de conteú- dos para considerar como a busca por novos modelos de negócio no jornalismo conduz suas atividades comerciais para além da venda de publicidade e assinaturas, discutindo desafios e implicações dessa prática. A hipótese é demonstrada com a descrição de operações de vendas de ingressos, livros, discos e filmes de modo vinculado à publicação de notícias e conteúdos jornalísticos de serviço. Questiona-se, por fim, de que forma essas ações comerciais podem afetar a autonomia e a isenção editorial no jornalismo.
Novos modelos de negócios e isenção editorial: um estudo sobre o jornalismo de serviço com base em operações de comércio eletrônico
Keywords: Journalism; Ecommerce; Publishing exemption; Jornalismo; E-commerce; Isenção editorial